Conundrum of mechanical knee symptoms: signifying feature of a meniscal tear?. Issue 5 (31st August 2018) - Thorlund, Jonas Bloch; Pihl, Kenneth; Nissen, Nis; Jørgensen, Uffe; Fristed, Jakob Vium; Lohmander, L Stefan; Englund, Martin
Abstract : Background: Mechanical knee symptoms are often considered important in the decision to perform knee arthroscopy on the suspicion of a meniscal tear. We investigated if presence of a meniscal tear at knee arthroscopy in adults is associated with presence of preoperative self-reported mechanical knee symptoms. Methods: We used data from Knee Arthroscopy Cohort Southern Denmark (KACS). KACS consists of patients aged 18 years or older referred to knee arthroscopy on the suspicion of a meniscal tear at four recruiting hospitals between 1 February 2013 and 31 January 2015. Of 1259 invited patients, 908 (72%) replied to the baseline questionnaire. With 91 patients excluded, the study sample consisted of 641 and 176 patients with and without a meniscal tear confirmed at surgery, respectively. Exposure was meniscal tear as determined by the knee surgeon during arthroscopy. Main outcomes were preoperative mechanical knee symptoms defined as self-reported catching/locking or self-reported inability to straighten knee fully. Results: 55% of all patients reported symptoms of catching/locking and 47% were unable to straighten their knee fully. Preoperative mechanical symptoms were equally prevalent in patients with and without a meniscal tear (prevalence ratio catching/locking 0.89, 95% CI 0.77 to 1.03, and inability to straighten knee fully, prevalence ratio 1.02, 95% CI 0.84 to 1.23). Interpretation: Patient-reported mechanical symptoms were equally common irrespective of presence or absence of a meniscal tear in patients undergoing arthroscopy for suspicion of a meniscal tear. Our findings suggest that mechanical knee symptoms have a limited value when considering indication for meniscal surgery. Trial registration number: NCT01871272 ; Results.